If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -3(5x + 5) Reorder the terms: 15 = -3(5 + 5x) 15 = (5 * -3 + 5x * -3) 15 = (-15 + -15x) Solving 15 = -15 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 15 + 15x = -15 + -15x + 15x Combine like terms: -15x + 15x = 0 15 + 15x = -15 + 0 15 + 15x = -15 Add '-15' to each side of the equation. 15 + -15 + 15x = -15 + -15 Combine like terms: 15 + -15 = 0 0 + 15x = -15 + -15 15x = -15 + -15 Combine like terms: -15 + -15 = -30 15x = -30 Divide each side by '15'. x = -2 Simplifying x = -2
| 12x-48=30 | | -4(-6x+8)=16 | | y=(-9)-2x | | -5(4t-3)+9t=2t-8 | | 12x-(9x-5)=17 | | 2(x-2)=5(x+3) | | 35n+25=625 | | 20x^3-17x^2+3x=0 | | .9x-6.2=.1 | | n=1.25n+6.25 | | x+(4+32)=32 | | 6x-4(2x+8)=36 | | 3x-9v=5+7v | | 16x+1=13-2x | | 4-3x+5x=6 | | 5x-3=3x-21 | | 49=-7t+(-7) | | 9m-5m+2=4m+2 | | X^2-6X-12X=0 | | 3y=-21+7x | | 2(x+1)(x+4)-(x-2)(x-2)=0 | | 6x+12-8x=20 | | 3*(x+2)-x= | | 15=3(5x+5) | | 12mn+4m+8mn+6m= | | (n-2)180= | | 2v^2+v+64=0 | | -4-4x+2x=-10 | | 1+4x=-31 | | a+-0.4=-3 | | 6(1+3d)=-8(-2m+5)-4 | | -3(4t-2)+7t=4t-4 |